Retirement of people with disabilities: importance and historical evolution (Research, Society and Development, 2022)
The objective of this work was to analyze the advantage created from a constitutional amendment no 47/2005, according to the private retirement due to the disability of the beneficiary and proposes critical reflections, with the starting point. The process of inclusion of people with disabilities in Lamarketwork and social security coverage. The methodology developed in this work was based on bibliographic references specialized in the matter, scientific articles and government legislation, using a hypothetical-deductive method of analysis, with a critical and interdisciplinary approach. In this proposal, the problem of doubt emerges from the use of the expression used in the constitutional text, especially in the face of other terminologies also used socially to qualify the situation of the phase, such as people with special needs. Why was it not the last employer in the last writing of the Constitutional Amendment text? Would it be more appropriate or not? This is a recent issue, with a view to the actual establishment of the benefit in 2013, with supplementary right 142/2013, regulated with joint articulation 01/2014.